A Multimetric Health Literacy Analysis of Autologous Versus Implant-Based Breast Reconstruction. (July 2020) - Chen, Daniel H.; Johnson, Anna Rose; Ayyala, Haripriya; Lee, Edward S.; Lee, Bernard T.; Tran, Bao Ngoc N.
Abstract : Background: Over the past decade, the demand for breast reconstruction has mirrored the rising incidence of breast cancer. Common postoncologic surgical options include autologous and implant-based reconstruction. Patient-directed health information for breast reconstruction can play a critical role in the decision-making process. This study comparatively evaluates the top online resources for autologous versus implant-based reconstruction using a multimetric health literacy analysis. Methods: The top 10 websites for autologous and implant-based reconstruction were identified using a Google search. A total of 20 unique links were appraised by 2 independent raters for understandability and actionability using the Patient Education Materials Assessment Tool and cultural sensitivity using the Cultural Sensitivity Assessment Tool. A Cohen κ for interrater reliability was calculated. Mean reading grade level and word complexity were also determined. Results: Websites for both autologous and implant-based modalities exceeded the recommended sixth- to eighth-grade reading level (12.4 and 12.1, respectively; P = 0.65). Mean understandability scores for each modality were low (60.5 and 62.5, P = 0.65). Autologous-based resources had a lower mean actionability score compared with implant-based materials (19.5 and 24, respectively; P = 0.04). Both reconstructive modalities met the threshold for acceptability for cultural sensitivity (2.79 and 2.58, P = 0.09). Conclusions: Our study revealed a chasm between the health literacy needs of the average adult and the quality of both implant-based and autologous breast reconstruction resources. Materials for both modalities were often too complex and failed to include tools to facilitate active decision making, particularly for autologous-based reconstruction. Strategies to improve materials should be patient centered and include simplification of reading grade level, incorporation of clear visual aids, and inclusion of procedural risks to promote patient comprehension, participation, and ultimately health outcomes.